Innovation and entrepreneurship - Bessant, J. R.; Tidd, Joseph (Chichester, West Sussex, UK : Wiley, 2011)
"Developed specifically for undergraduate students, Innovation and Entrepreneurship is an accessible, introductory text written primarily for those studying business and management but also engineering and science degrees with management courses.The book features contemporary applications such as services (public and private), innovation for sustainability, social entrepreneurship, innovation for development, and creating and capturing value from innovation and entrepreneurship. In this second edition the authors develop an explicit process model of entrepreneurship with clearer links between innovation and entrepreneurship"--Provided by publisher.
Keywords: Creative ability in business; Entrepreneurship